PERANCANGAN BUKU POP-UP MENGENAI MANFAAT BUAH DAN SAYUR UNTUK ANAK-ANAK - RUHI ELWARAK, Dini Faisal, S.Ds., M.Ds., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The aims of the design of the benefits of fruit and vegetable for children entitled Petualangan  Daisy bersama Peri Kebun was as medium of education and interaction in order to deliver the advantages of those fruits and vegetables. Afterward, it was expected that the children will interested in consuming fruits and vegetables because the nutrition in them is importance for development and growth of the children. Pop-up book was selected as one of the medium of learning for introducing children to the fruits and vegetables because it contains some interesting elements that will raise children’s enthuthiasm and passion in learning those knowledge.Method of analyzing data was 5W+1H technique in order to find the solution for the problem. Data were collected through interview and documentation. Pop-up book about the benefits of fruits and vegetables was designed through the theory of visual communication design, children psychology, medium of learning, pop-up book, illustration, color, layout and typography. Behind the pop-up book as the main medium, several stuffs like poster, x-banner, pin, sticker, coloring book, notebook and thumbler is served as the supporting medium.Kata kunci : buah dan sayur, buku pop-up, media interaktif, komsumsi.